Influence of bioactive glass and/or acellular dermal matrix on bone healing of surgically created defects in rat tibiae: A histological and histometric study - Ribeiro, Luciana Liarte Gasparini [UNESP]; Bosco, Alvaro Francisco [UNESP]; Nagata, Maria José Hitomi [UNESP]; De Melo, Luiz Gustavo Nascimento [UNESP] (My University, 2008)
Purpose: The purpose of this study was to histologically analyze the influence of bioactive glass and/or acellular dermal matrix on bone healing in surgically created defects in the tibiae of 64 rats (Rattus norvegicus, albinus, Wistar). Materials and Methods: A 4-mm x 3-mm unicortical defect was created on the anterolateral surface of the tibia. Animals were divided into 4 groups: C, control; BG, the defect was filled with bioactive glass; ADM, the defect was covered with acellular dermal matrix; and BG/ADM, the defect was filled with bioactive glass and covered with acellular dermal matrix. Animals were sacrificed at 10 or 30 days postoperatively, and the specimens were removed for histologic processing. The formation of new bone in the cortical area of the defect was evaluated histomorphometrically. Results: At 10 and 30 days postoperatively, groups C (39.65% ± 5.63%/63.34% ± 5.22%) and ADM (38.12% ± 5.53/58.96% ± 7.05%) presented a larger amount of bone formation compared to the other groups (P < .05). In the same periods, groups BG (13.10% ± 6.29%/29.5% ± 5.56%) and BG/ADM (20.72% ± 8.31%/24.19% ± 6.69%) exhibited statistically similar new bone formation. However, unlike the other groups, group BG/ADM did not present a significant increase in bone formation between the 2 time points. Conclusion: Based on these results, it can be concluded that all of the materials used in this study delayed bone healing in non-critical-size defects.
Keywords: Acellular dermis; Bioactive; Bioglass; Bone regeneration; Bone substitutes